A modified shuffled frog leaping algorithm for the bin packing problem - Go, Noel Anthony Mones (2008)
Bin packing is a mathematical way to efficiently fit elements into bins. Since the bin packing problem (BPP) is NP-hard, the most efficient known algorithms use heuristics to accomplish results which, although very good in most cases, may not be the optimal solution. Among the heuristics currently used are best fit, worst fit, next fit and the first fit. Metaheuristic methods applied to the BPP. The shuffled frog leaping algorithm (SFLA) I a population-based search algorithm were a population consists of frogs which are partitioned into subsets. However, an algorithm based on the uniform crossover and mutation operators of generic algorithm was used for the local search in the study instead of the particle swarm optimization-based local search of the SFLA since the BPP is a packing problem. Results showed that the MSFLA is a promising method to use in solving the BPP